Ficus spp.: Phytochemical composition and medicinal potential (Research, Society and Development, 2022)
This review aims to gather information on chemical compounds, biological activities and patents concerning parts of Ficus species, in order to contribute to the design of future studies. Systematic research was carried out on databases over the last five years. A total of 103 papers and 11 patents were found. Several species were investigated considering their chemical composition and biological properties. Organic acids, phenolic compounds, flavonoids, and terpenes were identified. Ficus carica was the most investigated species of the genus. Antioxidant, antimicrobial, anti-hyperglycemic, antidiabetes, anticancer and cytotoxic were the main reported activities, revealing their natural supplementary potential in contemporary diseases. Some of their chemical constituents presented pharmacological properties. These results suggest the potential of extracts and essential oil of Ficus genus in pharmacological industry. More studies still need to identify the compounds related to each property. Patents concerning parts of Ficus spp. involve different application areas, mainly cosmetics, food and pharmacology. This review may inspire investigations considering the development of new drugs, as well as new scientific and technological research using different parts of the Ficus genus.